PROSES LAYANAN PENDAFTARAN INTERNATIONAL MOBILE EQUIPMENT IDENTITY (IMEI) PADA KANTOR PENGAWASAN DAN PELAYANAN BEA DAN CUKAI (KPPBC) TIPE MADYA PABEAN C MATARAM - Wardiningsih, Reny (Jurnal Aplikasi Perpajakan, 2025)
This study aims to analyze the implementation of the IMEI registration service for telecommunication devices brought by passengers from abroad, as well as to evaluate the effectiveness of the service system through the utilization of the SIMETRIS application. This research employs a descriptive qualitative method with data collection techniques including observation, document review, and interviews. The theoretical framework encompasses public policy implementation, public service theory, and customs regulations related to IMEI. The results indicate that the IMEI registration procedure has been carried out in accordance with the provisions of the Director General of Customs and Excise Regulation Number PER-13/BC/2021 in conjunction with PER-7/BC/2023, supported by the CEISA PRM digital system and the SIMETRIS application. These innovations have proven to enhance service efficiency, data accuracy, and transparency. However, challenges remain, particularly regarding the low level of public understanding of the registration procedure and limited access to information. Therefore, more extensive public communication strategies and education efforts are needed to ensure optimal implementation of the policy.